Experimental Investigations on the Dynamic Behaviour of O-Type Wire-Cable Vibration Isolators - Hong-Xia Wang; Xian-Sheng Gong; Fei Pan; Xue-Jiang Dang (Shock and Vibration)
A series of periodic loading experiments were carried out on the O-type wire-cable vibration isolators. The isolators were loaded under shear, roll, and tension-compression loadings. When subjected to shear and roll loads, the restoring force-deformation curves generated by the isolators formed symmetric hysteresis loops. However, when the isolators were loaded with tension-compression loads, the isolator produced asymmetric hysteresis loops. It is found through the experiment that the dynamic characteristics of the isolator are determined by the loading amplitude as well as the geometric parameters of the isolator while they are almost independent of loading frequency within the testing frequency range. Based on the experimental data, the dynamic response of the isolator was modeled by a modified normalized Bouc-Wen model. The parameters of this model were identified through an identification procedure that does not involve any nonlinear iterative algorithms. Comparison between the identification results and the experimental data suggests that the identification method is effective. With the model and the identified parameters, the frequency response of an O-type wire-cable vibration isolator-mass system was evaluated. Typical nonlinear response behaviors were found when the isolator was used in tension-compression mode while the response appears to be similar to that of a linear system when the isolator was used in shear and roll mode.